2015
DOI: 10.1111/iej.12420
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of 2% chlorhexidine combined with proteolytic enzymes on biofilm disruption and killing

Abstract: The trypsin and CHX group with ultrasonics was significantly more effective at reducing bacterial viable counts and disrupting biofilm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 60 publications
0
21
1
Order By: Relevance
“…In another study, the same authors examined the synergistic effect of a disinfection regimen consisting of trypsin and proteinase K in combination with chlorhexidine on an endodontic multispecies biofilm model. Chlorhexidine used in combination with trypsin and proteinase K enhanced the biofilm killing effect of the entire disinfection regime [64]. In our study, proteinase K was able to remove most of the extracellular proteins and the treatment resulted in less dense biofilms compared to the control biofilm.…”
Section: Discussionmentioning
confidence: 46%
“…In another study, the same authors examined the synergistic effect of a disinfection regimen consisting of trypsin and proteinase K in combination with chlorhexidine on an endodontic multispecies biofilm model. Chlorhexidine used in combination with trypsin and proteinase K enhanced the biofilm killing effect of the entire disinfection regime [64]. In our study, proteinase K was able to remove most of the extracellular proteins and the treatment resulted in less dense biofilms compared to the control biofilm.…”
Section: Discussionmentioning
confidence: 46%
“…5 Other studies have shown that other topical preparations can be used to augment chlorhexidine as an antiseptic. Niazi et al 15 showed that the addition of a protease, (1% trypsin) with chlorhexidine was more effective at reducing biofilm production. We used aqueous chlorhexidine because of concerns about the cytotoxic effect of using an alcoholic antiseptic on the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have included species that are not typically found in primary or secondary/persistent infections, for example Staphylococcus epidermidis (Niazi et al . , ). It seems of limited relevance to include these strains in an endodontic biofilm model.…”
Section: Root Canal Biofilm Model Systems: Factors To Considermentioning
confidence: 99%